Hydroforming of sheet metal pairs from aluminium alloys - Novotny, Stefan; Hein, Philipp (Journal of Materials Processing Technology, 2001)
New production technologies like the hydroforming of sheet metal pairs have to be qualified for both steel and aluminium alloy sheets. While good mechanical properties and the excellent recyclability make sheets from aluminium alloys a good choice of material for lightweight construction, the lower formability compared to steel sheets raises various challenges for part manufacturing. Forming problems in the hydroforming process arise not so much from the material properties that determine the shape of the flow curve like the flow stress or the hardening exponent (n-value), but especially from the anisotropy of the aluminium material. This paper shows the process window, special requirements and potentials of the hydroforming of sheet metal pairs, using sheet material from heat treatable aluminium alloy AA 6016-T4. Different approaches for the enhancement of the formability of this material in the hydroforming process are outlined. © 2001 Elsevier Science B.V. All rights reserved.
LFT Import::2019-07-15 (909)
Keywords: Aluminium; Elevated temperature; Hydroforming; Lightweight construction